Age-Related Differences in Antimicrobial Resistance and MRSA in Urinary Tract Infections: Evidence from Pakistan - Syeda Fatima Rizvi, Zainab Mustafa, Tahir Mahmood, Nasir Khan, Tahir Shahzad Nawaz Babar, Zainab Awais (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Urinary tract infections (UTIs) remain among the most common bacterial infectionsacross all age groups in Pakistan, but age-related variation in antimicrobial resistance (AMR), especially methicillin-resistant